Diazine based ligand supported CoII3 and CoII4 coordination complexes: role of anions. (9th October 2018) - Sikdar, Yeasin; Goswami, Ranadip; Modak, Ritwik; Basak, Megha; Heras Ojea, María José; Murrie, Mark; Goswami, Sanchita
Abstract : Synthesis of triple helical CoII4 and double helical CoII3 from diazine-based ligands and their magnetic behavior rationalized by susceptibility measurements. Abstract : We report the synthesis and characterisation of a family of three CoII4 and two CoII3 complexes from a symmetrical diazine ligand, H2 hyda = N, N -bis(3-methoxy salicylidene)hydrazine. The metallic skeletons of all complexes reveal a nearly linear arrangement of Co II centers. The present results highlight the profound influence of anions on the structural outcome of a complex. Furthermore, distortion imposed by the twisted nature of the diazine-based ligand depends on the use of associated anions which results in triple helical CoII4 and double helical CoII3 entities. The Co II ions in complexes1–3 are antiferromagnetically coupled leading to an S = 0 ground state. In contrast, complexes4 and5 exhibit a magnetic ground state, but exhibit different behaviours at low temperatures due to differences in crystal packing and hence intermolecular interactions.